Fishery and biology of penaeid prawn Parapenaeopsis maxillipedo Alcock along Chennai (Madras) coast - Subrahmanian, V Thankaraj (Indian Journal of Fisheries, 2011)
Parapenaeopsis maxillipedo supported a steadily increasing fishery along the Chennai coast with the average annual catch of 326 t at the catch rate of 1.40 kg/hr contributing 11.8% of prawn landings in 1990-’99. The catches were more abundant in June-September and poor in summer months of April-May. Females were relatively more in number and larger in size. The overall sex-ratio for 1992- ’95 was 65.9 : 34.1% in favour of females. The length weight relationship was: Ln W = -3.9469 + 2.7077 Ln L for male and Ln W = -4.3493 + 2.8914 Ln L for female. The growth factors were: LÂ°Â° = 108.0 mm and K = 2.61/year for males LÂ°Â° = 117.8 mm and K = 2.21/year for females. The species had a short life span and only small fraction of the population could survive in the second year of life. Higher recruitment was recorded during February-March, June and September- October which was apparently linked to the greatbi spawning spells during June, October and February. The mortality rates were : Z = 7.4713, M = 4.3728 and F = 3.0985 for males and Z = 8.6939, M = 3.8301 and F = 4.8638 for females. These estimates gave an average exploitation rate of 0.49, that, with MSY of 304.7 t against the average catch of 326.4 t, indicated that the species had been in the level of optimum fishing intensity during the study period.